Sinergi UMKM Dan Ekonomi Indonesia: Sebuah Kajian Komprehensif Sebuah Perspektif Dan Implikasi - Mochammad Zulvikri (Jurnal Manajemen Bisnis Era Digital, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving Indonesia's economic progress, as they contribute significantly to job creation and increasing Gross Domestic Product (GDP). However, MSMEs are facing various challenges that hinder their ability to contribute optimally. This article aims to analyze the impact of MSMEs on Indonesia's economic growth, with an emphasis on policy perspectives and implications. The research uses a descriptive qualitative and quantitative approach, with secondary data obtained from the Central Statistics Agency (BPS), the Ministry of Cooperatives and SMEs, and relevant academic literature. The results show that MSMEs contribute more than 60% to Indonesia's GDP and create more than 97% of the workforce. However, challenges such as access to capital and technology hinder the growth of MSMEs. Policy recommendations include improving access to capital, technology support, and entrepreneurship training. Further research is needed to better understand the impact of MSMEs and to develop effective innovation and technology strategies.